2015
DOI: 10.1080/07347332.2015.1046011
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers' Illness Perceptions Contribute to Quality of Life in Head and Neck Cancer Patients at Diagnosis

Abstract: This study investigated the contribution of patient and caregiver illness perceptions to the quality of life of head and neck cancer (HNC) patients. Ninety-eight patients and their caregivers (n = 80) completed questionnaires at diagnosis. Caregivers' illness perceptions were significantly more negative than patients with respect to consequences, timeline, treatment, concern, and the emotional impact of HNC. The interaction between some patient and caregiver illness perceptions explained additional variance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 48 publications
4
26
0
Order By: Relevance
“…In a systematic review examining psychological functioning in HNC caregivers, caregivers were shown to experience significant anxiety and were especially susceptible to distress 6 months after treatment (Longacre, Ridge, Burtness, Galloway, & Fang, 2012). Recent studies have examined caregiver adjustment further, finding that caregivers have higher recurrence fears (Hodges & Humphris, 2009), worse illness outlook (Richardson, Morton, & Broadbent, 2015), and more post-traumatic stress disorder (Posluszny et al, 2015) compared to patients. Research has identified some HNC caregivers at risk for poor outcomes, including those caring for patients with more needs (Chen et al, 2009) or worse symptoms during treatment (Badr, Gupta, Sikora, & Posner, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review examining psychological functioning in HNC caregivers, caregivers were shown to experience significant anxiety and were especially susceptible to distress 6 months after treatment (Longacre, Ridge, Burtness, Galloway, & Fang, 2012). Recent studies have examined caregiver adjustment further, finding that caregivers have higher recurrence fears (Hodges & Humphris, 2009), worse illness outlook (Richardson, Morton, & Broadbent, 2015), and more post-traumatic stress disorder (Posluszny et al, 2015) compared to patients. Research has identified some HNC caregivers at risk for poor outcomes, including those caring for patients with more needs (Chen et al, 2009) or worse symptoms during treatment (Badr, Gupta, Sikora, & Posner, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have shown that patients feel more confident and hopeful when conversations focus on patient needs and involve discussions where both patient and relatives are present [149,155,156]. The patients in Paper I who reported that they did receive adequate information felt reassured, a finding which is also in line with earlier studies [157][158][159]. Reassurance may entail individual medical information and improved understanding of the condition [157].…”
Section: Information and Breaking Newssupporting
confidence: 80%
“…The patients in Paper I who reported that they did receive adequate information felt reassured, a finding which is also in line with earlier studies [157][158][159]. Reassurance may entail individual medical information and improved understanding of the condition [157].…”
Section: Information and Breaking Newssupporting
confidence: 76%
“…This type of informational intervention should ideally be delivered early after the patient's diagnosis, and preferably face to face (Richardson et al . ). It is also important for health professionals to be conscious that some caregivers may be uncertain about how to talk to professionals, and professionals may therefore may need to proactively bring up these discussions with caregivers (Longacre et al .…”
Section: Discussionmentioning
confidence: 97%
“…Head and neck caregivers may in fact be more distressed by head and neck cancer than the patients themselves (Richardson et al . ,b). Around a third of head and neck cancer relative/friends indicate that they believe that caring is a significant burden on caregivers (Precious et al .…”
Section: Introductionmentioning
confidence: 99%